Impact Of Self Help Group On Members In Bidar DistrictKarnataka (India) (International Journal of Scientific Research and Management (IJSRM), 2015)
Self-help group are necessary to overcome exploitation, create confidence for the economic selfreliance of rural people, particularly among women who are mostly invisible in the social structure. These groups enable them to come together for common objective and gain strength from each other to deal with exploitation, which they are facing in several forms. A group becomes the basis for action and change. It also helps buildings for mutual trust between the promoting organization and the rural poor through constant contact and genuine efforts. Thus, self-help group disburses microcredit to the rural women for the purpose of making them enterprising women and encouraging them to enter into entrepreneurial activities. Credit needs of the rural and urban and urban poor women are fulfilled totally through the SHGs. SHGs enhance equality of status of women as participation, decision makers and beneficiaries in the democratic, social and culture spheres of life. The main objective of this paper is to evaluate the performance of the SHGs and the attitude of the members of the SHGs towards economic impact, social impact and psychological impact.